Simple Experiment of Doppler Effect Using Smartphone Microfon Sensor - Adam Malik; Widiastuti Ledgeriani Mugiri; Rizki Zakwandi; Sani Safitri; Tia Juliani (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2020)
Doppler effect is the physical phenomena in which the emitted frequency is a source of change at a time when accepted by the detector due to relative movement of the detector towards the source of the wave or vice versa. This research aims to identify the Doppler effect symptoms by utilizing sensors found in smartphones. This research uses experimental method that combine the mechanical instruments and microphone smartphone sensor as measurement tool. The mechanical instruments used are a smartphone with the help of frequency sound generator software, Physics Toolbox, the camera as an instrument of data collectors, and Tracker as a motion analyzer software. Based on the results of the experiments, the author retrieved the value of the error and the standard deviation of each of the observed symptoms. The symptoms of Doppler effect upon source moving closer and moving away when the silent observer shows the error value of 0.04 % and 0.1185 % respectively with a standard deviation of 0.018 and 1.005. In addition, the experiment on Doppler effect as the source is staying still and as the observer approaching the source provides error value of 8.60 % and standard deviation of 13.501. As for the experiment on Doppler effect as the source and the observers are approaching each other displays the error value of 4.31 % and the standard deviation of 0.087. Overall, this experiment generates error value of 3.267 % and standard deviation of 3.665, inferring that the experiments conducted are accurate and precise in representing the Doppler effect phenomenon. Based on the results of this experiments, the researcher recommends to carry out practicum on Doppler effects with the help of smartphone sensors.